Malawi : Ninth Review Under the Extended Credit Facility Arrangement and Request for Waivers for Nonobservance of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Malawi's Ninth Review Under the Extended Credit Facility Arrangement and Request for Waivers for Nonobservance of performance criteria. Real GDP growth is expected to range between 4-5 percent in 2017 owing to a good agricultural harvest and its expected spillovers to other sectors of the economy. Growth prospects, however, will be constrained by persistent power blackouts, water shortages, and access to credit. Real growth is expected to gradually increase over the medium term as macroeconomic conditions stabilize and investment and consumption levels rise. The outlook remains challenging, reflecting uncertainties related to weather conditions, the impact of the fall armyworm infestation on food crops and risks of policy slippages.